Efetividade da gestão pública municipal e direitos humanos da mulher em situação de violência em Breves – Pará - MIRANDA, Raquel Monteiro de (Universidade Federal do Pará, 2019)
In this master’s thesis, it is brought up for discussion the issue about the effectiveness of public management in the municipality of Breves, state of Pará, concerning women’s public policy, focusing confrontation with domestic and family violence, as well with human rights for women from Breves. It is worth mentioning the existence of a large amount of women threatened with violence in this municipality that remains in privacy, whereas those ones who are able to expose it do not receive specialized assistance. For this purpose, this study analyzes management work and its participation in public policies aiming at guaranteeing women’s rights; assesses services and agencies for women threatened with violence; and characterizes social, economic and cultural profile of women complaining about violence; and verifies how municipal public management, through public policies, contributes to decrease women’s social vulnerability. It uses concepts of public management, public policies, violence, and human rights from the theoretical apparatus researched. Methodologically, it is classified as descriptive and exploratory, characterized as quantitative and qualitative. It is based on biographical, document and field research. It uses techniques for semi-structured interviews, applied to the agents of assistance service for women threatened with violence; and for questionnaires for data collecting, applied to a sample of female victims. Besides document, observational, and statistical survey. It is possible to infer that the context of public policies for women does not favor its effectiveness. The actions carried out do not provide comprehensive solutions, and are not thought nor directed to this population. Despite the improvement of regulatory instruments, the assistance provided is still not enough. This study is, therefore, considered relevant since it contributes to the knowledge about public policy development and instruments that promote women’s rights